PRIMARY HYPOPHYSITIS WITH HYPOPITUITARISM IMPROVING WITH HIGH DOSE STEROIDS - Ooi, Xin-Yi; Lim, LL; Lim, QH; Vethakkan, SR DB; Ratnasingam, J; Ibrahim, L; Paramasivam, SS (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION A 39-year-old female presented with an 8-month history of severe headaches, amenorrhea for 6 months, increased thirst and weight loss. She consulted a neurologist for migraine and was subsequently referred to an endocrinologist when her MRI showed a pituitary lesion. There was no visual impairment. RESULTS Investigations on admission: Free T4 11.7 pmol/L (11.5-22.7) TSH 0.11 mIU/L (0.55-4.78) IGF-1 267 ng/ml (63.4-223) ACTH <5 pg/ml AM cortisol <14 nmol/L LH <0.1IU/L(0.5-16.9) FSH 2.8IU/L (1.5-9.1) Estradiol 75 pmol/L (205-786) Prolactin 511 mIU/L (59-619) MRI of the pituitary gland showed a clearly thickened pituitary stalk abutting the optic chiasm with heterogeneous enhancement along the stalk and base of the hypothalamus and loss of posterior bright spot. The pituitary enhances peripherally with a slight hyperintensity on T1-weighted images, signifying proteinaceous or inflammatory changes. There was no dural tail sign. She was diagnosed with hypophysitis and was started on IV methylprednisolone 500 mg OD for 3 days. She developed overt polyuria after initiation of steroids and required regular desmopressin. As she is young with hypopituitarism and diabetes insipidus, she was given prednisolone 50 mg OD as per the protocol from Chiloco et al from Rome with a tapering dose planned over 13 months. In the study by Chiloco et al, this regime showed a 50-70% improvement in hormonal deficiencies compared to conservative treatment. This patient had resumption of her menses after 3 months despite still requiring regular desmopressin. There was improvement in her pituitary function with FT4 16.1 pmol/L, TSH 0.55mIU/L, LH 2IU/L, FSH 2.2IU/L and estradiol 193 pmol/L. Repeat MRI showed marked reduction in her stalk thickening. CONCLUSION High dose and prolonged steroids are an effective treatment to improve hormonal outcome in a patient with primary hypophysitis